Spectral imaging of FRET‐based sensors reveals sustained cAMP gradients in three spatial dimensions. Issue 10 (3rd September 2018) - Annamdevula, Naga S.; Sweat, Rachel; Griswold, John R.; Trinh, Kenny; Hoffman, Chase; West, Savannah; Deal, Joshua; Britain, Andrea L.; Jalink, Kees; Rich, Thomas C.; Leavesley, Silas J.
Abstract: Cyclic AMP is a ubiquitous second messenger that orchestrates a variety of cellular functions over different timescales. The mechanisms underlying specificity within this signaling pathway are still not well understood. Several lines of evidence suggest the existence of spatial cAMP gradients within cells, and that compartmentalization underlies specificity within the cAMP signaling pathway. However, to date, no studies have visualized cAMP gradients in three spatial dimensions (3D: x, y, z ).This is in part due to the limitations of FRET‐based cAMP sensors, specifically the low signal‐to‐noise ratio intrinsic to all intracellular FRET probes. Here, we overcome this limitation, at least in part, by implementing spectral imaging approaches to estimate FRET efficiency when multiple fluorescent labels are used and when signals are measured from weakly expressed fluorescent proteins in the presence of background autofluorescence and stray light. Analysis of spectral image stacks in two spatial dimensions (2D) from single confocal slices indicates little or no cAMP gradients formed within pulmonary microvascular endothelial cells (PMVECs) under baseline conditions or following 10 min treatment with the adenylyl cyclase activator forskolin. However, analysis of spectral image stacks in 3D demonstrates marked cAMP gradients from the apical to basolateral face of PMVECs. Results demonstrate that spectral imaging approaches can be used to assess cAMP gradients—and in general gradients in fluorescence and FRET—within intact cells. Results also demonstrate that 2D imaging studies of localized fluorescence signals and, in particular, cAMP signals, whether using epifluorescence or confocal microscopy, may lead to erroneous conclusions about the existence and/or magnitude of gradients in either FRET or the underlying cAMP signals. Thus, with the exception of cellular structures that can be considered in one spatial dimension, such as neuronal processes, 3D measurements are required to assess mechanisms underlying compartmentalization and specificity within intracellular signaling pathways. Abstract : 3‐dimensional cAMP spatial gradients were measured in cells utilizing 4D (x, y, z, λ) hyperspectral imaging. Shown here is a 3‐dimensional reconstruction of cAMP concentrations in a pulmonary microvascular endothelial cell (PMVEC), 300 s after treatment with 50 µM forskolin (adenylyl cyclase activator). Hot colors (orange‐red) represent high cAMP concentration – localized to apical regions. Cool colors (green‐blue) represent low cAMP concentration – localized to basolateral regions. These data illustrate that agonist‐induced axial spatial gradients in cAMP concentration can form within PMVECs.